Microplastics in Cronius ruber: Links to Wastewater Discharges - Sofía Huelbes; May Gómez; Ico Martínez; Raül Triay-Portella; Miguel González-Pleiter; Alicia Herrera (Animals)
Microplastic pollution in the ocean is a growing problem. It affects the entire ecosystem and, therefore, the species that inhabit it. Plastics can be filtered or ingested by organisms, entering and negatively affecting individuals. Among the populations affected are crustaceans. In previous studies, fibers have been found mainly in the stomach contents of these animals, although other types, such as pellets, have also been found. This study examines the presence of microplastics in Cronius ruber, an invasive crab species in the Canary Islands, and investigates their potential links to nearby wastewater discharges. A total of 63 crabs were sampled from four beaches in Gran Canaria in 2021, and their stomach contents were analyzed through alkaline digestion, filtration, and micro-Fourier transform infrared spectroscopy (micro-FTIR). Microplastics were detected in 52% of individuals; the particles averaged 0.7 ± 0.5 mm in length, with an average of 1.73 ± 1.02 particles per crab. Fibers constituted 89% of the microplastics, with blue and black being the predominant colors. Rayon, commonly used in textiles, was the most frequently identified polymer (52%), highlighting the role of wastewater from laundry processes as a significant pollution source. Beaches close to unauthorized wastewater discharges, such as Anfi del Mar (n = 3) and El Puertillo (n = 32), showed the highest contamination levels, with a frequency of occurrence (FO) of microplastic particles of 67% and 58%, respectively. Playa de Las Nieves was the one with the lowest contamination level (n = 22), with a frequency of occurrence of microplastic particles of 41%. This is the first study to document microplastic ingestion in C. ruber, raising concerns about its ecological presence and the potential bioaccumulation of contaminants in marine ecosystems. Further research is essential to understand the long-term consequences of microplastic exposure on invasive species and their possible roles in pollutant transfer through food webs.